A new species of the genus Storenomorpha Simon from Vietnam (Araneae, Zodariidae) - Grismado, Cristian J.; Ramírez, Martín J. (Zootaxa, 2004)
Storenomorpha paguma sp. nov. (Araneae: Zodariidae: Storenomorphinae) is described from specimens collected in Ha Tinh and Ngh An Provinces, Vietnam. Genitalic features suggest its close relationship with S. reinholdae Jocqu & Bosmans and S. nupta Jocqu & Bosmans.